Pharmacovigilance in Libya: Current Status and Future Trends - Atia, Ahmed (Indian Journal of Pharmacy Practice)
Libya, like other countries around the world, are working to develop vigorous pharmacovigilance systems. While the majority of the developed countries have established efficient pharmacovigilance systems, Libya still lack the basic structure to create such systems. This commentary emphases on the necessity of establishing pharmacovigilance system and focus on its current status and future prospect in Libya.
Keywords: Pharmacovigilance; Libya; Adverse drug reaction; Healthcare; Medicines.